Fish consumption and exposure to persistent organochlorine compounds, mercury, selenium and methylamines among Swedish fishermen - Svensson, B-G; Nilsson, A; Jonsson, E; Schütz, Andrejs; Åkesson, Bengt; Hagmar, Lars (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'This study assessed dietary habits and exposure to selenium, persistent organochlorine compounds, methylmercury, and methylamines among Swedish fishermen.Methods Two hundred and fifty randomly selected subjects from a cohort of 2896 fishermen from the Swedish east coast (Baltic Sea) and 8477 fishermen from the west coast (Skagerrak and Kattegatt) were interviewed along with 250 referents. Subgroups of fishermen and referents from different coastal areas were also selected for blood and urine sampling.Results The interview data showed that fishermen ate almost twice as much fish as the 250 referents from the general population. The blood levels of mercury were twice as high, and the plasma selenium levels were 10--15% higher in the fishermen than in the referents. There was, however, no difference between the fishermen`s cohorts with respect to these variables. Fishermen from the east coast ate more fatty fish than fishermen from the west coast, and they also had higher blood levels of persistent organochlorine compounds such as polychlorinated biphenyls and polychlorinated dibenzo p-dioxins and furans (present in fatty fish species in the Baltic Sea) than both the westcoast fishermen and the referents.Conclusion A cohort of Swedish eastcoast fishermen might be a suitable study base for epidemiologic studies on the mortality and cancer morbidity associated with dietary exposure to persistent organochlorine compounds.
Keywords: consumption; exposure; fish; fish consumption; fisherman; mercury; methylamine; PCP; persistent organochlorine compound; polychlorinated biphenyl; polychlorinated dibenzo-p-dioxin; polychlorinated dibenzofuran; selenium; Sweden